High-performance semitransparent perovskite solar cells with solution-processed silver nanowires as top electrodes1. Issue 5 (7th February 2015) - Guo, Fei; Azimi, Hamed; Hou, Yi; Przybilla, Thomas; Hu, Mengyao; Bronnbauer, Carina; Langner, Stefan; Spiecker, Erdmann; Forberich, Karen; Brabec, Christoph J.
<x xml:space="preserve">Abstract</x> Semitransparent perovskite devices with FF up to 70% and PCE of 8.5% are demonstrated using spray-coated AgNWs as top electrodes.